2017
DOI: 10.1177/0363546517738002
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Medial Patellofemoral Ligament Origin in the Skeletally Immature Knee: An Anatomic Study

Abstract: This information shows anatomic variation of the MPFL origin with age, with older specimens having a footprint that was more proximal and anterior than younger specimens. Customization of the surgical technique might be considered based on patient age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…For pediatric patients, there has been a great deal of investigation into the relationship of the MPFC to the distal femoral physis. There has been wide variability in findings, with the average origin of the MPFC occurring 4.7-10 mm distal to the physis [7,8]. The superior-most fibers of the MPFC origin commonly overlie the physis [7,8].…”
Section: Anatomy and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…For pediatric patients, there has been a great deal of investigation into the relationship of the MPFC to the distal femoral physis. There has been wide variability in findings, with the average origin of the MPFC occurring 4.7-10 mm distal to the physis [7,8]. The superior-most fibers of the MPFC origin commonly overlie the physis [7,8].…”
Section: Anatomy and Functionmentioning
confidence: 99%
“…There has been wide variability in findings, with the average origin of the MPFC occurring 4.7-10 mm distal to the physis [7,8]. The superior-most fibers of the MPFC origin commonly overlie the physis [7,8]. The origin may migrate closer to the physis in adolescence [8].…”
Section: Anatomy and Functionmentioning
confidence: 99%
“…The diagnosis of tears of the anterior horn of the meniscus by MRI is sometimes different from that obtained by arthroscopic examination. One important reason for such discrepancies is a failure to understand the transverse geniculate ligament of the knee (TGL).The knee joint is the largest and most complex joint of the human body [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Beginning with his first paper, ''Anterior Calcaneal Osteotomy of Symptomatic Juvenile Pes Planus,'' in 1984, 3 his prolific research continued unabated through the present year. 15 Allen was particularly interested in the welfare of young athletes, leading to important articles on the subjects of osteochondritis dissecans 5,[8][9][10] and anterior cruciate ligament reconstruction in the skeletally immature patient. 2 In an era when many American surgeons felt that randomized trials in orthopaedic surgery were unfeasible, Allen showed us that they could indeed be done.…”
mentioning
confidence: 99%